2019
DOI: 10.7287/peerj.preprints.27890v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophages of Klebsiella spp., their diversity and potential therapeutic uses

Abstract: Klebsiella spp. are commensals of the human microbiota, and a leading cause of opportunistic nosocomial infections. The incidence of multi-drug resistant (MDR) strains of Klebsiella pneumoniae causing serious infections is increasing, and K. oxytoca is an emerging pathogen. Alternative strategies to tackle infections caused by these bacteria are required as strains become resistant to last-resort antibiotics such as colistin. Bacteriophages (phages) are viruses that can infect and kill bacteria. They and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 1 publication
0
37
0
3
Order By: Relevance
“…In fact, Klebsiella is one of the most prophage-rich species, comparable to E.coli and Yersinia enterocolitica with a medium of nine prophages per genome [ 27 ]. The phages used in the current study belong to so called K32 phages [ 21 , 28 ]. A known characteristic of phage K32 and related phages which belong to Podoviridae is the presence of capsule-polysaccharide specific depolymerase.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Klebsiella is one of the most prophage-rich species, comparable to E.coli and Yersinia enterocolitica with a medium of nine prophages per genome [ 27 ]. The phages used in the current study belong to so called K32 phages [ 21 , 28 ]. A known characteristic of phage K32 and related phages which belong to Podoviridae is the presence of capsule-polysaccharide specific depolymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella sp. is usually involved in nosocomial infections, such as urinary and respiratory tract infections as well as infections of wounds and soft tissue (Herridge et al, 2020). Klebsiella pneumoniae and Klebsiella oxytoca are the most common pathogens in genus Klebsiella that have rapidly become global threat.…”
Section: Biochemical Characterization and Bacterium Identificationmentioning
confidence: 99%
“…In addition, they exhibit far fewer side effects compared to the antibiotics [7]. At least 70 K. pneumoniae phages have been isolated and characterized to date [8]. However, very few K. pneumoniae phages have been studied in vivo using mouse, rat and pig models [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few K. pneumoniae phages have been studied in vivo using mouse, rat and pig models [9][10][11][12][13]. Apart from these animals, the virulence of K. pneumoniae has also been evaluated in other non-conventional models such as amoeba and zebrafish to mitigate limitations in the mouse, rat and pig models such as high cost, specialized facilities and ethical concerns [8]. It has been shown that only certain K. pneumoniae strains were able to infect zebrafish and cause mortality.…”
Section: Introductionmentioning
confidence: 99%